The very hungry caterpillar - Carle, Eric. (New York : Scholastic, 1969)
Follows the progress of a hungry little caterpillar as he eats his way through a varied and very large quantity of food until, full at last, he forms a cocoon around himself and goes to sleep. Die-cut pages illustrate what the caterpillar ate on successive days.
G2
Keywords: Toy and movable books -- Specimens; Caterpillars -- Fiction; Toy and movable books